(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The dimension of competition in the retail market is high and demands a need to oversee shopping malls properly and understand the general consumer behavior amid visits at shopping mall as far as their principle explanations behind visiting the mall and attitude so as to pull in shopping mall guests to visit these malls. Till date it is being commanded by small and unorganized entrepreneurs like Khirana shops, standalone stores, boutiques, traditional family business stores and so on. The sorted out retail industry in India is to grow 40 percent every year and would significantly increase or multiple times in size. The purchase of goods or services incorporates various factors that could influence every choice. Customer satisfaction is progressively perplexing and much more significant for retailers today than in past. Be that as it may, with the developing global economic forces, new economic policies, FDI relaxations and one of a kind marketing techniques the new sort of retailers like shopping malls will in general snare the consumers even in Tier II and Tier III towns. While the progress is going on at global dimension in different structures, the shopping behavior of consumer is additionally prone to change with the developing decisions and trends. Shopping in malls has turned into a noteworthy recreation action. Composed retail sector is developing at fast speed, more occupations are being made, town plans are getting modernized, and therefore the consumer behavior as well. In this Research Study, we studied about the development of shopping malls recently, their importance and the Consumer Perceptions towards them.